PENGARUH STRUKTUR ASET, RISIKO BISNIS DAN UKURAN PERUSAHAAN DENGAN STRUKTUR MODAL SEBAGAI VARIABEL INTERVENING PADA PERUSAHAAN SUB SEKTOR KIMIA TBK PERIODE 2018-2021 - Siti Maratus Sholikha; Fatimah Riswati (Fakultas Ekonomi dan Bisnis Universita Wijaya Putra Surabaya, 2023)
This research aims to examine and analyze the effect of asset structure, business risk and firm size on firm value with capital structure as the intervening variable in the Chemical Sub-Sector Company Tbk for the 2018-2021 Period. The sampling technique used in this research is purposive sampling technique and obtained as many as 8 companies as research samples with a population of 18 companies in the chemical sub sector. Data analysis was carried out using descriptive statistics with the SmartPLS tool. Based on data analysis, it shows that asset structure has no significant effect on firm value, business risk has a significant effect on firm value, firm size has no significant effect on firm value, asset structure has no significant effect on capital structure, business risk has a significant effect on capital structure, Firm size has no significant effect on capital structure, capital structure has no significant effect on firm value, asset structure has no significant effect on firm value through capital structure, business risk has no significant effect on firm value through capital structure, and firm size has no significant effect on firm value.